Do Ethical Leadership, Visibility, External Regulation, and Prosocial Impact Affect Unethical Behavior? Evidence From a Laboratory and a Field Experiment. (September 2019) - Belle, Nicola; Cantarelli, Paola
This article investigates the effects that ethical leadership, visibility of task performance and conduct, external regulation, and prosocial impact have on revealed and observed preferences for unethical behavior in public administration settings. Experiment 1 engages university students in a laboratory experiment and observes misconduct in two tasks. Ethical messages and visibility reduced subjects' dishonesty in declaring the outcome of the task that affected their pay but did not influence the self-reported performance in the exercise tied to raising donations. For the latter task, ethical leadership and visibility interacted negatively. Monetary incentives and prosocial impact increased individuals' unethical behavior consistently across the two tasks. Experiment 2 is a discrete choice experiment exploring public sector workers' preferences for misbehaving on the job. While ethical leadership and visibility did not affect their preferences, a significant financial gain and the opportunity to improve the life of many people increased the willingness to behave unethically.